KHSRP knockdown inhibits papillary renal cell carcinoma progression and sensitizes to gemcitabine - Song, Wei; Zhang, Heng; Lu, Yi; Zhang, Houliang; Ni, Jinliang; Chang, Lan; Gu, Yongzhe; Wang, Guangchun; Xu, Tianyuan; Wu, Zonglin; Wang, Keyi (Frontiers in Pharmacology, 2024)
Patients diagnosed with papillary renal cell carcinoma (pRCC) exhibit a high rate of clinical metastasis; however, the underlying molecular mechanism is unclear. In this study, KH-type splicing regulatory protein (KHSRP) participated in pRCC progression and was associated with metastasis.It was positively correlated with the hallmark of epithelial-mesenchymal transition. KHSRP inhibition effectively alleviated the cellular function of migration and invasion. Additionally, KHSRP knockdown inhibited the proliferative ability of pRCC cells. A pharmaceutical screening was based on the KHSRP protein structure. Gemcitabine (Gem) decreased KHSRP expression.UIO-66@Gem@si-KHSRP (UGS) nanoparticles (NPs) were prepared for targeted delivery and applied in both in vitro and in vivo experiments to explore the clinical transition of KHSRP. UGS NPs exhibited better performance in inhibiting cellular proliferation, migration, and invasion than Gem. Additionally, the in vivo experiment results confirmed their therapeutic effects in inhibiting tumor metastasis with excellent biosafety. The silico analysis indicated that KHSRP knockdown increased cytotoxic cell infiltration in the tumor microenvironment to potentiate anti-tumor effects.Thus, KHSRP can promote pRCC progression as an oncogene and serve as a target in clinical transition through UGS NP-based therapy.